Exploring Palembang Cultural Context through PMRI in Mathematics Learning: A Systematic Literature Review - E.I. Pusta Siligar; Ratu Ilma Indra Putri; Zulkardi Zulkardi; Hapizah Hapizah (Jurnal Inovasi Matematika, 2025)
The current cultural context has become a significant focus in mathematics education, serving not only as a bridge to formal understanding but also as a means of cultural preservation. This study aims to analyse the use of Palembang's cultural context in mathematics education through the Indonesian Realistic Mathematics Education (PMRI) approach. The analysis was conducted on articles indexed in Scopus and Google Scholar based on publication year, content, methods, student skills developed, and research findings. Data analysis techniques were based on the PIECES framework (Planning, Identifying, Evaluating, Collecting/Elaborating, Explaining, and Summarising). From the selection process, 20 articles that met the inclusion criteria were obtained. The analysis results showed that the dominant cultural context of Palembang included traditional food (pempek), traditional fabrics (songket and jumputan), and trading activities on the Musi River. The most frequently studied mathematical topics were geometry and algebra, with the design research method used as an approach to design learning and develop media such as worksheets, educational videos, and evaluation instruments. The students' ability most frequently focused on was conceptual understanding. These findings provide significant contributions to educators and researchers in developing context-based cultural mathematics learning through the PMRI approach.